Recent Advances of Therapeutic Strategies Based on the Molecular Signature in Non-Syndromic Congenital Neutropenia - Mohammad Darvish; Mohammadreza Nazer; Hamzeh Shahali; Ebrahim Karimi; Alireza Dadashi; Seyed Zia Hejripour; Majid Noori (Institute of Medico-legal Publications Pvt Ltd, 2021)
Neutropenia has been defined to be classified into transient and chronic forms based upon duration andacquired or congenital forms. Chronic neutropenia is considered as congenital, cyclic, autoimmune andidiopathic categorizes, where congenital and cyclic categories are hereditary forms of neutropenia, but theidiopathic and autoimmune are known as acquired neutropenia. In the present review, we focus highly onthe genetic subtypes of non-syndromic congenital neutropenia and therapeutic strategies regarding to recentevidence. All aspects of molecular pathogenesis and biology have not been clarified so far; therefore, furtherin-depth understanding of the molecular mechanisms is needed to reveal roles of molecular mechanisms,and pathways involved in the development of congenital neutropenia and to provide a basis for achievingnovel therapeutic strategies.